Pengaruh Citra Merek, Promosi, Dan Kemudahan Transaksi Terhadap Keputusan Penggunaan E-Wallet DANA Gen Z Di Kabupaten Tangerang - Ken Sabardiman Soetjipto; Abdur Rochman; Naim Naim; R. Didik Heriyantoro; Meslo Pardede; Vera Lupi Nurpratiwi; Thomas Bobby Ronaldo (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the influence of brand image, promotion, and ease of transactions on the decision to use the DANA e-wallet among Generation Z in Tangerang Regency. The main issue examined is how these three variables contribute to shaping preferences and decisions to use digital financial services among the increasingly technology-adapted younger generation. The research method used was a quantitative approach, using a survey technique using a questionnaire to Gen Z respondents who use the DANA e-wallet. Data were analyzed using multiple linear regression to test the partial and simultaneous effects between variables. The results show that brand image, promotion, and ease of transactions simultaneously have a significant influence on the decision to use the DANA e-wallet. Partially, ease of transactions has the most dominant influence, followed by brand image and promotion. Interpretation of the results indicates that practical factors and user experience are the main determinants of e-wallet adoption by Gen Z. Therefore, it can be concluded that improving service quality, appropriate promotional strategies, and strengthening brand image are crucial for increasing the decision to use the DANA e-wallet among Generation Z.